Waste management and recycling practices of the urban poor: a case study in Kuala Lumpur city, Malaysia - Murad, Md. Wahid; Siwar, Chamhuri (SAGE Publications, 2007)
This Study assesses waste management and recycling practices of the urban poor households residing as squatters and in low-cost flats of Kuala Lumpur city, Malaysia. To attain the objective, the study employed some statistical techniques such as t-tests of equality of means, one-way analysis of variance, chi-squared 'likelihood ratio' tests, and simple descriptive statistics. The statistical techniques were used to determine and analyse the factors that significantly influence the environmental behaviour of the urban poor concerning solid waste management, particularly their recycling practices. The findings of the study show that the urban poor and low-income communities have been proved to behave in ways that are consistent with and conducive to environmentally friendly solid waste management. This study provides evidence that the urban poor and low-income communities are the main recyclers, re-users, and source-reducers of their household solid waste. The study, however, suggests that policies should be formulated to focus on promoting knowledge, education, and the skills of the urban poor and, in addition, to empower them as a means of improving their quality of life.